1998
DOI: 10.1021/jm9707232
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically and Conformationally Restrained Cinnamoyl Compounds as Inhibitors of HIV-1 Integrase:  Synthesis, Biological Evaluation, and Molecular Modeling

Abstract: Various cinnammoyl-based structures were synthesized and tested in enzyme assays as inhibitors of the HIV-1 integrase (IN). The majority of compounds were designed as geometrically or conformationally constrained analogues of caffeic acid phenethyl ester (CAPE) and were characterized by a syn disposition of the carbonyl group with respect to the vinylic double bond. Since the cinnamoyl moiety present in flavones such as quercetin (inactive on HIV-1-infected cells) is frozen in an anti arrangement, it was hoped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 39 publications
1
105
0
3
Order By: Relevance
“…The 3-D images of 3’ and 5’ clearly attests to the planar conformation between the aromatic ring, the vinylic double bond, and the carbonyl group. Studies have shown that when cinnamoyl-based structures were synthesized and characterized by a syn disposition of the carbonyl group with the vinylic double bond, they specifically inhibited the enzymatic reactions associated with HIV-1 integrase (IN) [36]. …”
Section: Resultsmentioning
confidence: 99%
“…The 3-D images of 3’ and 5’ clearly attests to the planar conformation between the aromatic ring, the vinylic double bond, and the carbonyl group. Studies have shown that when cinnamoyl-based structures were synthesized and characterized by a syn disposition of the carbonyl group with the vinylic double bond, they specifically inhibited the enzymatic reactions associated with HIV-1 integrase (IN) [36]. …”
Section: Resultsmentioning
confidence: 99%
“…26 In the cyclohexanone (6b) and the cycloheptanone (6c) derivatives the molecules are more distorted and the conformers with out of plane aryl group to the C=C double bonds are preferred. 27,6 The stereostructure is practically the same in the 4 and the 7-11-type dienones. In the monosubstituted cyclanones 5 the cinnamoyl moiety is distorted even in the molecules of 5a with 5-membered ring: in the solid state the plane of the aryl ring deviates from that of the C=C double bond by 23 º .…”
mentioning
confidence: 94%
“…1 Previously, we described the preparation of saturated and partially saturated 1,3-thiazines using E-2-arylidenecycloalkanones as starting materials. 2,3 Some diarylidenecycloalkanones have been reported to possess cytoprotective 4,5 as well as HIV-1 integrase 6 and factor Xa inhibitor activities 7 . These effects were found to depend on the ring size (stereochemistry) and the substituents of the aromatic rings.…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, chalcone was first synthesized by a hydroxyl-protection method and a consequent condensation reaction was performed in a base environment [27,28]. Then, different nitrogen atoms side chains (heterocyclic azo and open chain amino) were attached to the A ring by Mannich reactions.…”
Section: Introductionmentioning
confidence: 99%